Karakteristik Sarang dan Kepadatan Populasi Orangutan (Pongo pygmaeus wurmbii) Di Zona Khusus Laboratorium Alam Hutan Gambut Taman Nasional Sebangau Kalimantan Tengah: Orangutan (Pongo pygmaeus wurmbii) Nest Characteristics and Population Density in The Special Zone of The Peat Natural Forest Laboratory of Sebangau National Park Central Kalimantan - Rizal, Moh; Sinaga, Fani Delima Sari; Octavianus, Robby; Junaedi, Ajun; Luhan, Gimson (HUTAN TROPIKA, 2023)
This study aimed to identify nest density and orangutan (Pongo pygmaeus wurmbii) population as well as nest characteristics (nest tree type, nest tree height, nest tree diameter, nest age class, nest location) in the special zone of the Peat Forest Nature Laboratory (LAHG) of Sebangau National Park, Central Kalimantan. The research used the strip transect method with the length of each line ± 1000 m and a width of 20 m on each right and left side of the line as many as 5 transect lines. The objects of observation were orangutans, orangutan nests, and nest trees along the transect lines. The results showed that the average density of orangutan nests in the LAHG special zone of Sebangau National Park in Central Kalimantan was 375.17 nests/km2 with an estimated orangutan population density of 0.987 individuals/km2. Characteristics of orangutan nests found in the research location include: the most common tree species used as a place to make orangutan nests is Tarantang (Campnosperma coriaceum (Jack) Hallier f.) from the Anacardiaceae family. The height and diameter of the most dominant trees used as orangutan nests ranged from 11-15 m and 11-20 cm, respectively. The height of orangutan nests from the ground ranged from 11-15 m, the class of nests included class B, and the position of nests included category 4.